1989
DOI: 10.1021/ac00194a008
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for radical anion formation during liquid secondary ion mass spectrometry analysis of oligonucleotides and synthetic oligomeric analogs: a deconvolution algorithm for molecular ion region clusters

Abstract: It is shown that one-electron reduction is a common process that occurs in negative ion liquid secondary ion mass spectrometry (LSIMS) of oligonucleotides and synthetic oligonucleosides and that this process is in competition with proton loss. Deconvolution of the molecular anion cluster reveals contributions from (M-2H).-, (M-H)-, M.-, and (M + H)-. A model based on these ionic species gives excellent agreement with the experimental data. A correlation between the concentration of species arising via one-elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1993
1993
2000
2000

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Furthermore, semi-empirical MNDO calculations for the electron affinities of glycerol, thiodiglycol and thioglycerol give large negative values which implies rather convincingly that these molecules are unlikely to scavenge electrons. 43 Only in the case of HEDS where the calculated electron affinity24 was slightly positive (0.07 eV) is there any possibility of electron scavenging. This is supported by pulse radiolysis experiment^.^' The lower extent of dehalogenation observed in other sulfur-containing matrices may be explained by the bombardment-induced formation of thiyl radicals which are known to have oxidizing proper tie^.^^ This idea introduces the concept that the capacity of the matrix to quench reductive processes may not depend uniquely on the properties of the intact matrix molecule.…”
Section: Lsi Ms Liquid Matrix Compounds Used In This Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, semi-empirical MNDO calculations for the electron affinities of glycerol, thiodiglycol and thioglycerol give large negative values which implies rather convincingly that these molecules are unlikely to scavenge electrons. 43 Only in the case of HEDS where the calculated electron affinity24 was slightly positive (0.07 eV) is there any possibility of electron scavenging. This is supported by pulse radiolysis experiment^.^' The lower extent of dehalogenation observed in other sulfur-containing matrices may be explained by the bombardment-induced formation of thiyl radicals which are known to have oxidizing proper tie^.^^ This idea introduces the concept that the capacity of the matrix to quench reductive processes may not depend uniquely on the properties of the intact matrix molecule.…”
Section: Lsi Ms Liquid Matrix Compounds Used In This Studymentioning
confidence: 99%
“…42 The electron affinity of NBA could be approximated from the experimental value obtained for an analogous compound, methyl nitrobenzene, which has an electron affinity of 0.9 eV.39 This value is also in accord with the calculated value of 0.92 eV for NBA. 43 The ability of NBA to inhibit reduction processes in FAB/LSIMS, including dehalogenation, is well documented. ",' 1,24*44*45 In their work, Miller and cow o r k e r~~~ have suggested that this property of NBA is related to the fact that the matrix can act as an electron sink and thus mitigate chemical damage.…”
Section: Lsi Ms Liquid Matrix Compounds Used In This Studymentioning
confidence: 99%
“…To determine quantitatively the contribution of redox processes to the intensity distribution of peaks in the parent ion cluster, the natural isotopic abundances and the background signal must be deconvoluted from the overall peak intensities measured in this mass region. Deconvolution procedures that have been presented in the literature [4,18] are performed by solving a determined set of linear equations and then calculating a least-squares fit. Both of these procedures, however, are vulnerable to errors due to chemical interference because a determined set of equations has only one solution that may be mathematically correct yet physically insignificant.…”
mentioning
confidence: 99%
“…The reaction seems even more favored with the free nucleotide than with cytosine bases incorporated in ssDNA. To compare our results with earlier work,38–41 2′‐deoxyadenosine was also examined and found to be reductively hydrogenated when analyzed alone using 2,5‐DHB. In fact, 2′‐deoxyadenosine is reduced to form [M + 4H] + , as noted previously by Stemmler et al 40 However, in spite of these data, it remains clear from the in‐source decay fragments that cytosine is the reduced base in the oligonucleotides that were examined.…”
Section: Resultsmentioning
confidence: 60%
“…Previous work in fast atom bombardment (FAB) and MALDI has demonstrated that one electron reductions37, 38 and reductive hydrogenations38–41 of oligonucleotides occur. While Laramee et al examined the products of one‐electron reductions and subsequent reactions, only poly‐A and poly‐T were examined in detail 38. In FAB experiments, Cerny and Gross indicated that all nucleosides are reductively hydrogenated during desorption from glycerol matrix and that adenosine yields the most reduced product 39.…”
Section: Introductionmentioning
confidence: 99%